2017
DOI: 10.1007/s13300-017-0244-9
|View full text |Cite
|
Sign up to set email alerts
|

Indian Injection Technique Study: Injecting Complications, Education, and the Health Care Professional

Abstract: IntroductionUsing the Indian and rest of world (ROW) injection technique questionnaire (ITQ) data, we address key insulin injection complications.MethodsIn 2015 we conducted an ITQ survey throughout India involving 1011 patients. Indian values were compared with those from 41 other countries participating in the ITQ, known here as ROW.ResultsMore than a quarter of Indian insulin users described lesions consistent with lipohypertrophy (LH) at their injection sites and approximately 1 in 5 were found to have LH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 43 publications
(36 reference statements)
4
45
2
3
Order By: Relevance
“…Extremely lean patients should be using a skin fold to inject even with a 4 mm and 5 mm needle. 8 In the present study 59% of patients used needle length of 6 mm, and a majority of 79% patients practiced injecting into the skinfold (Table 2 and 4).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Extremely lean patients should be using a skin fold to inject even with a 4 mm and 5 mm needle. 8 In the present study 59% of patients used needle length of 6 mm, and a majority of 79% patients practiced injecting into the skinfold (Table 2 and 4).…”
Section: Discussionmentioning
confidence: 53%
“…7 This method of correct rotation of the injection site was practiced by nearly 3/4 th of the patients in the present study (Table 3), which is comparable with the study conducted by Kalra et al 8 Cleaning of injection site with sterile cotton swabs dipped in alcohol or water prior to injection is of utmost importance to ensure prevention of healthcare-associated infections. 8 In the present study, it was found that only 62% of the patients practiced cleansing of skin before injection (Table 4). Some longer-acting insulins contain a predetermined ratio of either crystalline insulin and solvent or crystalline insulin and rapid-acting soluble insulin.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Patient was managed using talk, inspect and educate strategy followed by our endocrinology clinic considering the high prevalence of insulin-related lipohypertrophy in Indian patients 2. Readdressing correct injection technique is very important to curb lipohypertrophy and its consequences.…”
Section: Descriptionmentioning
confidence: 99%